Hubungan Antara Sikap Kerja Dengan Keluhan Low Back Pain Pada Perawat Rawat Inap Di Rumah Sakit PKU Muhammadiyah Surakarta - ISLAMI, DIAN DINI, dr. Hardjanto., MS.Sp.Ok, Sri Darnoto., SKM.MPH (2016)
A job as a nurse is a job that has a complex activity ranging from the activity of lifting, pushing, pulling, carrying, moving or holding and everything related to the patient. If such activity is carried out continuosly with an ergonomic work posture as well as high load can cause disorders of the muscle and will have an impact on a complaint of low back pain. This research aims to know the relationship between the working attitude with a complaint of low back pain in nurses in hospital inpatient PKU Muhammadiyah of Surakarta. Research methods this observational method with cross sectional approach. The population in this research is the inpatient nurse on ward 4 recommended by hospitals PKU Muhammadiyah of Surakarta as much as 70 nurses. The selection of the sample using calculation formulas and calculation of proportion as many as 45 nurses. Bivariat analysis using Chi-Square. The result of statistical tests for relationship work attitude with a complaint of low back pain is obtained a value of p=1,000. From the result it can be concluded that there is no relationship between the working attitude with a complaint of low back pain in nurses inpatient hospital PKU Muhammadiyah of Surakarta. Key words: Nurse, Work Attitude, a complaint of Low Back Pain